Analisis Budaya Organisasi Pada Panti Asuhan Anak Daarul Hasanah Kabupaten Karawang - Sumiati, Neni; Tuhagana, Aji; Triadinda, Dexi (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the organizational culture applied by the Daarul Hasanah Children's Orphanage, Karawang Regency, analyze the management's performance strategy and evaluate what efforts need to be considered to improve performance at the Daarul Hasanah Children's Orphanage, Karawang Regency. This research was conducted using a qualitative descriptive method, namely through a literature study conducted by studying literature related to the research topic, as well as field studies conducted through and conditions in an institution. Based on the results of the overall evaluation, the organizational culture at the Daarul Hasanah Children's Orphanage, Karawang Regency, is not optimal. By implementing a strategy to grow it by implementing it in a positive orphanage environment, applying it in a way of communicating effectively, giving appreciation for achievements, paying attention to the welfare of the orphanage, this research seeks to reformulate the organizational culture strategy by using Maslow's theory of need hierarchies as a basis for the administrators of the orphanage to carry out tasks according to their duties and functions. Based on the research that has been done regarding the Analysis of Organizational Culture at the Daarul Hasanah Karawang Children's Orphanage, in the role of orphanage administrators in supporting the continuation of Children's Education the Board acts as foster parents or substitute parents for foster children by forming the nature, mentality of foster children that aims guide, educate, direct, and regulate the behavior of foster children get from their respective parents.